Evaluation of the frequency and pattern of local recurrence following intersphincteric resection for ultra-low rectal cancer - W. Abdel-Gawad; A. Zaghloul; I. Fakhr; M. Sakr; A. Shabana; M. Lotayef; O. Mansour (Journal of the Egyptian National Cancer Institute, 2014)
Introduction: Abdomino-perineal resection has been the standard treatment for rectal tumors located ⩽5 cm from the anal verge. Recently, intersphincteric resection became a valid option which preserves the bowel continuity with better functional outcome. Aim: Is to evaluate the oncological and functional outcome alongside the associated surgical morbidity in patients with T1-3 rectal cancer, who underwent intersphincteric resection (ISR). Patients & methods: Between the years 2006 and 2011, 55 patients with invasive rectal adenocarcinoma, T1-3 lesions, located 2–5 cm from the anal verge underwent ISR with total mesorectal excision. When inevitable, complete. ISR was performed, otherwise partial ISR was done. All T3 patients underwent total meso-rectal excision (TME) while some had lateral lymph node dissection (LND) with concomitant pelvic autonomic nerve preservation (PANP). Results: Among the 55 patients, 21 (38.1%) patients were T1-2 and 34 (61.9%) patients were T3. The tumor location range was 0–5 cm from the anal verge (median 2.3 cm). Partial or complete ISR was done for 35 (63.6%) and 20 (36.4%), respectively. Patients were followed for a median of 1.5 years (range 1–4.6 years). The 3 year local recurrence and distant metastasis free rates were 85.2% and 85.6%, respectively. All the 3 local recurrences occurred in T3 patients group, and had positive circumferential resection margins. Overall 3-year disease-free survival was 82.6%; while the overall 3-year survival was 88.7%. Conclusion: Intersphincteric resection with TME does not affect the local recurrence or overall survival rate in early rectal cancer T1-2 & 3, with preservation of bowel continuity and better life quality.